1999
DOI: 10.1021/je9900068
|View full text |Cite
|
Sign up to set email alerts
|

Solubilities of Some Hydroxyxanthone Derivatives in Supercritical Carbon Dioxide

Abstract: The equilibrium solubilities of four hydroxyxanthone derivatives have been measured in supercritical carbon dioxide using a simple and reliable static method. The measurements were performed in the pressure range 74.0−354.6 bar at the temperatures 32, 45, 55, 65, and 75 °C. The order of solubility observed for the compounds used was discussed in terms of their possible intra- and intermolecular H-bonds and polarities. The measured solubilities were correlated using a semiempirical model. The calculated results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…The poor consistency is mainly limited to the data points obtained at high pressures limits of the isotherms, which are close to the melting points of the drugs (melting point depression is obtained at higher pressures). Similar results have been observed for anthracene and pyrene [21] and xanthene derivatives [22]. By removing the solubility results at pressures of 213 and 385 bar good results are obtained.…”
Section: Resultssupporting
confidence: 82%
“…The poor consistency is mainly limited to the data points obtained at high pressures limits of the isotherms, which are close to the melting points of the drugs (melting point depression is obtained at higher pressures). Similar results have been observed for anthracene and pyrene [21] and xanthene derivatives [22]. By removing the solubility results at pressures of 213 and 385 bar good results are obtained.…”
Section: Resultssupporting
confidence: 82%
“…They found that the solubility of hydroxycoumarins and especially dihydroxycoumarin in supercritical CO 2 is very low. Studies of other dihydroxy compounds, such as 1,6-dihydroxyxantone and 1,8-dihydroxy-9,10-antraquinone showed that their solubility in supercritical CO 2 is also very low, most likely due to intermolecular H-bond interactions [17,18]. The solubility of esculetin was determined in comparatively low density CO 2 at pressures up to 25 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…Such a retrograde (crossover versus pressure effect) behavior has already been reported for different organic compounds. [7][8][9][11][12][13]17,18 At pressures that are less than the crossover region, solvent densities are decreased by small increases in temperature; because the density effect is dominant in this region, the solubility will decrease with rising temperature. At higher pressures, the solvent density is less dependent on temperature, so that the increase in solubility is primarily due to the higher vapor pressure of the solid.…”
Section: Resultsmentioning
confidence: 99%
“…Some researchers have reported extensive measurements of the solubility of disperse dyes in supercritical carbon dioxide. Disperse dyes usually used for the dyeing of polyester textiles are divided into two main groups, i.e., azo-dyes and anthraquinone derivatives. In recent years, we have reported the solubilities of some 9-10-anthraquinone, , hydroxyxanthone, and 9-anthrone drivatives in supercritical carbon dioxide. In this study, the solubility of the four recently synthesized anthraquinone derivative disperse dyes i.e., 1-amino-2-methyl-9,10-anthraquinone (A1), 1-amino-2-ethyl-9,10-nthraquinone (A2), 1-amino-2,3-dimethyl-9,10-anthraquinone (A3), and 1-amino-2,4-dimethyl-9,10-anthraquinone (A4) in supercritical carbon dioxide have been measured over a wide range of pressure and temperature.…”
Section: Introductionmentioning
confidence: 99%